Предмет: Математика, автор: RiskulbekovTimur

((a^3/4+b^3/4)(a^3/4-b^3/4)÷(a^1/2-b^1/2)-(ab)^1/2)×2÷(a+b)^1/2=2

Ответы

Автор ответа: mefody66
0
Будем решать по частям.
1) (a^{3/4}+b^{3/4})(a^{3/4}-b^{3/4})=a^{3/2}-b^{3/2} (разность квадратов).
2)  frac{a^{3/2}-b^{3/2}}{a^{1/2}-b^{1/2}} = frac{(a^{1/2}-b^{1/2})(a+(ab)^{1/2}+b)}{a^{1/2}-b^{1/2}} =a+(ab)^{1/2}+b (разность кубов).
3) (a+(ab)^{1/2}+b-(ab)^{1/2})*2=2(a+b)
4) 2(a+b):(a+b)^{1/2}= frac{2(a+b)}{ sqrt{a+b} } =2 sqrt{a+b}
Если это равно 2, то  sqrt{a+b}=1;a+b=1;b=1-a
Похожие вопросы